PERAN KUALITAS LABA DALAM MENDUKUNG KINERJA KEUANGAN DALAM MENINGKATKAN NILAI PERUSAHAAN - Ana Mardiana; Excel Limbunan; Lavenia Leonard (Universitas Islam Bandung, 2023)
The aim of this research was to investigate the impact of free cash flow, leverage, and profitability to earnings quality and the impact of earnings quality to firm value. The population used is manufacturing companies listed in the Indonesian Stock Exchange (IDX) for period of 2017-2019. Number of samples are 64 companies each year chosen with purposive sampling method. This research uses documentary data, i.e. the annual report and financial statements. Path analysis used to analyze the data and mediation hypothesis analysed by using sobel test. The results of this research indicate that free cash flow and leverage have a positive and not significant impact on earnings quality. In contrast, profitability has a negative and significant impact on earnings quality. The results also show that free cash flow, leverage, and profitability have a positive and significant effect on firm value. Conversely, earnings quality has a positive and not significant impact on firm value.